2024
DOI: 10.1007/s12032-023-02282-5
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-loaded piperlongumine nanoparticles and kaempferol enhance the anti-cancer action of doxorubicin in targeting of Ehrlich solid adenocarcinoma: in vivo and in silico modeling study

Fawziya A. R. Ibrahim,
Neveen A. Hussein,
Aisha Y. M. Soliman
et al.

Abstract: Doxorubicin is a chemotherapeutic drug that generates free radical-induced toxicities. Natural agents are used to potentiate or ameliorate the toxicity of chemotherapy. None of the studies investigating whether antioxidants or prooxidants should be used with chemotherapy have addressed their efficacy in the same study. Therefore, the aim of this study was to investigate the potential synergy between doxorubicin and two natural rarely in vivo studied anticancer agents; the antioxidant “Kaempferol” and prooxidan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 43 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…An increase in the expression of the Bcl2 gene was also observed. Additionally, it was shown that the pro-tumorigenic gene CyPA and the pro-autophagic gene BECN1 were significantly decreased after KEM administration [ 157 ]. Studies conducted on mice with oral cavity cancer showed that tissue samples from mice treated with KEM exhibited a significant increase in apoptosis compared to the control group.…”
Section: Protective Effects Of Flavonoids Against Cancer: In Vivo Evi...mentioning
confidence: 99%
“…An increase in the expression of the Bcl2 gene was also observed. Additionally, it was shown that the pro-tumorigenic gene CyPA and the pro-autophagic gene BECN1 were significantly decreased after KEM administration [ 157 ]. Studies conducted on mice with oral cavity cancer showed that tissue samples from mice treated with KEM exhibited a significant increase in apoptosis compared to the control group.…”
Section: Protective Effects Of Flavonoids Against Cancer: In Vivo Evi...mentioning
confidence: 99%